Design, Simulation and Practical Experimentation of Miniaturized Turbine Flow Sensor for Flow Meter Assessment - Ifedapo Abdullahi, Salami; Hadi Habaebi, Mohamed; Abd Malik, Noreha (Bulletin of Electrical Engineering and Informatics, 2019)
Flow sensors are very essential in many aspects of our daily lives. Many of the industrial processes need a very consistent flow sensor to monitor and check for irregularities in their system. Therefore, flow sensor is an important tool for advanced operation in industrial environment. In this paper, the design and development of a 3D fabricated flow sensor was carried out using SolidWork 3D CAD. SolidWork Flow Simulation was used to model the effect the turbine flow sensor would have on a constant flowing water while MATLAB Simulink flow graph was created to visualize the effect of turbine flow sensor response with voltage input. Afterwards, the design was 3D printed using UP Plus 2 3D printer. The experimentation involved selection of sensors, coding to control the turbine flow sensor and automatic data logging and storage. During the design phase, the sensors and actuators were assembled using locally sourced material. Subsequently, under controlled laboratory environment, the turbine flow sensor was tested using a DC motor which was programmed to control the revolution per minute(rpm) of the turbine flow sensor. The rpm and velocity of the turbine flow meter was measured and stored in a database via Microsoft Excel using Cool Term Software. A total number of 517 readings were analysed to evaluate the performance of the turbine flow sensor. The result shows that the turbine flow meter is responsive to the motor input voltage and yielded accurate measurement of rpm and velocity of turbine flow meter.